Upaya Penegakan Hukum Terhadap Perkara Kecelakaan Anak yang Menyebabkan Korbannya Meninggal Dunia - Annas, Gilang Kresnanda (Jurnal Hukum Caraka Justitia, 2023)
The high number of traffic accidents today is still a difficult problem to solve. Moreover, the current traffic problem also involves children in acts of violation of the law. Not even a few traffic violations committed by children can be fatal to other people and even to the loss of one's life. The results of this study discuss penal and non-penal measures that can be taken by the police in dealing with child accident cases that cause the victim to die. An approach that is deliberative to obtain justice using diversion and restorative principles is chosen to create justice for both perpetrators and victims.